Sintesis Literatur: Efektivitas Sistem Dukungan Berjenjang (Three-Tier Support) dalam Menjamin Kesejahteraan Emosional di Sekolah Inklusif - Rida Hermawati; Risbon Sianturi; Taopik Rahman (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Your Emotional well-being (child well-being) is a crucial foundation for children's learning success in inclusive schools, yet its implementation is often not systematically structured. This research aims to synthesize literature regarding the effectiveness of implementing a MultiTiered System of Supports (MTSS) or Three-Tier Support in ensuring children's emotional well-being in inclusive environments. The research method used is a literature review, analyzing 20 reputable scientific articles from Google Scholar, ERIC, and Science Direct databases within the 2021 to 2026 period. The results of the literature synthesis indicate that the tiered support model provides an effective framework through three levels of intervention: Tier 1 as universal support for all students, Tier 2 as targeted group interventions for at-risk children, and Tier 3 as intensive individual support. These findings confirm that tiered systems are capable of creating an emotional safety net responsive to diverse child needs, reducing anxiety levels, and increasing resilience in inclusive schools. The implications of this research emphasize the importance of standardizing emotional support protocols so that teachers can provide targeted interventions without compromising classroom inclusivity